Aerosolized surfactant in neonatal respiratory distress syndrome: Phase I study. (July 2019) - Sood, Beena G.; Cortez, Josef; Kolli, Madhuri; Sharma, Amit; Delaney-Black, Virginia; Chen, Xinguang
Abstract: Background: Treating respiratory distress syndrome (RDS) with intratracheal surfactant requires endotracheal intubation and mechanical ventilation, (MV) with their attendant risks. Use of non-invasive respiratory support in the delivery room averts the need for MV but delays surfactant administration. Objective: We hypothesized that aerosolized surfactant is feasible and safe in infants 24 0/7 –36 6/7 weeks gestational age (GA) with RDS, receiving non-invasive respiratory support. Design/methods: In an unblinded Phase I study, sequentially enrolled infants with RDS stratified by GA received increasing doses (100 or 200 mg/kg of phospholipid) and dilutions (12.5 or 8.3 mg/ml) of surfactant using a jet nebulizer. Infants were monitored clinically and with cerebral oximetry. Results: Seventeen infants were enrolled. Age at start of first dose and dose duration were 4.9 (3.4–10.1) and 2.1 (1.0–2.8) hours respectively. Two infants in the lowest GA stratum (24 0/7 –28 6/7 ) required intubation within 2 h after the first dose. Fifteen infants completed the study; 13 received two doses. Infants tolerated the aerosol treatment well. No other significant adverse events were identified. Parental permission for cerebral oximetry was obtained in 16 infants. In the two infants who later exited the study, values prior to start of aerosolized surfactant were lower compared to 14 infants who completed the study (p = 0.0835), increased after start of study intervention (p = 0.0105) and decreased after intubation (p = 0.0003). Conclusions: We have demonstrated the feasibility and safety of aerosolized surfactant in preterm infants receiving non-invasive respiratory support. The treatment was well tolerated by infants and clinical caregivers. Highlights: Use of non-invasive respiratory support in the delivery room can avoid the need for intubation in 50% of preterm infants. Infants requiring intubation after failure of primary NIV receive delayed surfactant and have higher rates of morbidity. A combination of early non-invasive respiratory support with early surfactant may lead to further improvement in outcomes. We have demonstrated the feasibility of administering aerosolized surfactant to spontaneously breathing preterm infants. These results will inform the design of future trials to identify the most effective strategy for aerosolized surfactant.